-7x+8+4x=-3(x-3)-1

Simple and best practice solution for -7x+8+4x=-3(x-3)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+8+4x=-3(x-3)-1 equation:


Simplifying
-7x + 8 + 4x = -3(x + -3) + -1

Reorder the terms:
8 + -7x + 4x = -3(x + -3) + -1

Combine like terms: -7x + 4x = -3x
8 + -3x = -3(x + -3) + -1

Reorder the terms:
8 + -3x = -3(-3 + x) + -1
8 + -3x = (-3 * -3 + x * -3) + -1
8 + -3x = (9 + -3x) + -1

Reorder the terms:
8 + -3x = 9 + -1 + -3x

Combine like terms: 9 + -1 = 8
8 + -3x = 8 + -3x

Add '-8' to each side of the equation.
8 + -8 + -3x = 8 + -8 + -3x

Combine like terms: 8 + -8 = 0
0 + -3x = 8 + -8 + -3x
-3x = 8 + -8 + -3x

Combine like terms: 8 + -8 = 0
-3x = 0 + -3x
-3x = -3x

Add '3x' to each side of the equation.
-3x + 3x = -3x + 3x

Combine like terms: -3x + 3x = 0
0 = -3x + 3x

Combine like terms: -3x + 3x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| N=24 | | X+74=146 | | X-23=0 | | 7+10+x=2x+26 | | 5x=25-x | | 630/10 | | x+x+1=-222 | | (3x-5)(7x+3)=0 | | -5-(15x-1)=2(7x-160-y) | | 14-19x+3x^3=0 | | 7p + 2 = 5p + 8 | | 5(1)=-4+6 | | .18(6)+.03X=.06(6+X) | | 70=6*8 | | 1/3(8x-1)+19=94 | | y=100-10y-10 | | 2x-3(6.666666667)=-24 | | 105=7*11 | | 3x+7-8x+2=-36 | | x+x+1=299 | | 5x-4(y)=13 | | 2(n-3)-11=7 | | m+4=-15 | | 76-3x=15+16 | | -2k+5=-7-k+3k | | 2x+3(5(x-1)+2)=42 | | 298/2 | | 5x-(4y)=13 | | 21-22x+x^2=0 | | lnx(lnx+2)=0 | | 20=3(w+2)+2 | | m+3-5=5m+3m+7 |

Equations solver categories